Effectiveness and priority of irradiation and six NSAIDs in prevention heterotopic ossification after total hip arthroplasty: a network meta-analysis of randomized controlled studies - Yang, Fei; Wen, Lei; Chen, Changshun; Zhao, Qiao; Feng, Zhiwei; Ran, Bin; Luo, Xuwei; Xiao, Dongqin; Fang, Qifan (Frontiers in Pharmacology, 2025)
BackgroundHeterotopic ossification (HO) involves the ectopic deposition of bone in soft tissues, frequently occurring as a complication post-hip trauma or surgery. To prevent HO following total hip arthroplasty (THA), irradiation has been extensively employed, alongside the use of nonsteroidal anti-inflammatory drugs (NSAIDs). Given the extensive range of NSAIDs available, determining the most effective NSAID or irradiation protocol for prophylaxis continues to be a matter of debate.MethodsAdhering to the PRISMA guidelines, a comprehensive search was conducted across PubMed, Embase, Cochrane Library, and Web of Science to identify relevant randomized controlled trials. To minimize bias in literature evaluation, two authors independently searched and assessed the articles. In cases of disagreement, a third author was consulted. We strictly implement the inclusion and exclusion criteria. Using the criteria for assessing bias in the Cochrane Collaboration Network, two writers independently evaluated the quality of the included studies. We systematically extracted and assessed data according to the level of evidence presented in the articles. A Bayesian network meta-analysis (NMA) was implemented to evaluate and contrast the efficacy of irradiation and six distinct NSAIDs in preventing HO after THA. The results were computed using the GEMTC package in R (V.4.4.1). The consistency of the model was tested using nodal analysis. The priority of drug efficacy was comprehensively evaluated using rank probability and the surface under the cumulative ranking curve (SUCRA). Stata 16 was used to assess publication bias, and sensitivity analysis was performed using the one-by-one elimination method. The protocol for this study was officially registered with the International Platform of Registered Systematic Review and Meta-analysis Protocols (INPLASY).ResultsA total of 461 studies were identified, and 17 studies were finally included in the analysis. The meta-analysis incorporated data from 3,014 patients: 629 administered ibuprofen, 54 with naproxen, 117 receiving celecoxib, 426 on indomethacin, 295 treated with diclofenac, 45 on etoricoxib, 522 subjected to irradiation, and 926 serving as controls. These trials reported an average age ranging from 59 to 75 years, with males comprising 31.2%–63% of subjects. The total incidence rate of HO in all control groups was 55.2%. In terms of effectiveness, compared with the control, four strategies showed a low incidence of HO, including naproxen (OR = 0.08, 95% CrI 0.01–0.60), indomethacin (OR = 0.13, 95% CrI 0.04–0.41), diclofenac (OR = 0.06, 95% CrI 0.01–0.29), and irradiation (OR = 0.08, 95% CrI 0.02–0.3). Diclofenac was more beneficial than ibuprofen (OR = 0.10, 95% CrI 0.01–0.97). The probabilities derived from the surface under the cumulative ranking curve (SUCRA) algorithm are as follows: Diclofenac (78.0%), etoricoxib (71.6%), irradiation (67.3%), naproxen (66.7%), indomethacin (53.2%), celecoxib (38.8%), ibuprofen (18.6%), and a control group (6.8%). Because stronger evidence supports the efficacy of diclofenac. The most likely ranking for the effectiveness of preventing HO after THA is as follows: Diclofenac > etoricoxib > irradiation > naproxen > indomethacin > celecoxib > ibuprofen.ConclusionIn terms of preventive efficacy, diclofenac and etoricoxib demonstrated the most favorable performance in preventing HO after THA within this network meta-analysis. Irradiation, naproxen, and indomethacin are also satisfactory options, while ibuprofen is ineffective. Given the advantages shown by etoricoxib and celecoxib, further randomized controlled trials are recommended to clarify their effects. Our conclusions require confirmation through additional high-quality studies.